2018
DOI: 10.1111/spc3.12382
|View full text |Cite
|
Sign up to set email alerts
|

Why do we do what we do? The Attention–Readiness–Motivation framework

Abstract: According to many theories of motivation, the principal driver of human behavior is the affectively driven valuation of actions. Actions are valued by maximizing the difference between stimulus value (the benefits and costs inherent in the stimulus outcome that is the expected result of a given action) and action costs (the effort required to perform that action). However, such accounts have difficulty explaining why individuals act inconsistently in what appear to be comparable situations and often act in way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Related to our third proposition, there is strong empirical evidence that suggests that increased attention with respect to a particular option, increases the probability of selection for that option (Milosavljevic et al, 2012; Krajbich et al, 2010; Shimojo et al, 2003; Suri et al, 2018; Suri & Gross, 2015; for a review see Orquin & Loose, 2013). This empirical evidence is bolstered by influential drift-diffusion accounts of decision-making (Krajbich, 2019) according to which decision-makers accumulate evidence in favour of an alternative when attending to it, and that the speed of accumulation is a function of the value of the alternative relative to other alternatives in the choice set, which is called the bias rate or drift rate.…”
Section: Biased Attention As a Driver Of Sqbmentioning
confidence: 82%
“…Related to our third proposition, there is strong empirical evidence that suggests that increased attention with respect to a particular option, increases the probability of selection for that option (Milosavljevic et al, 2012; Krajbich et al, 2010; Shimojo et al, 2003; Suri et al, 2018; Suri & Gross, 2015; for a review see Orquin & Loose, 2013). This empirical evidence is bolstered by influential drift-diffusion accounts of decision-making (Krajbich, 2019) according to which decision-makers accumulate evidence in favour of an alternative when attending to it, and that the speed of accumulation is a function of the value of the alternative relative to other alternatives in the choice set, which is called the bias rate or drift rate.…”
Section: Biased Attention As a Driver Of Sqbmentioning
confidence: 82%
“…We close this work with the observation that while the study of three addend sums is firmly rooted in the mathematical cognition literature, it has the potential to open a new domain for research into value-based decision making (Rangel, Camerer, & Montague, 2008;Suri, Shine, & Gross, 2018) and in other domains. Researchers in several sub-disciplines study contexts in which decision-making process unfolds via a comparison of the costs and benefits on offer.…”
Section: Discussionmentioning
confidence: 87%
“…Participants were shown either a negative image or a neutral image (Suri & Gross, 2015; Suri, Sheppes, & Gross, 2015; Suri, Shine, & Gross, 2018) from a database of affective images, classified into positive, neutral, and negative categories. In each of 40 trials, they were shown a negative or neutral image as a default.…”
Section: Simulations Of Empirical Findings Using Iacmentioning
confidence: 99%